Plasma Fibrinogen Level in Chronic Obstructive Pulmonary Disease and Its Correlation with GOLD Severity Staging - Gyawali, Achyut; Bam, Niraj; Pant, Pankaj; Das, Santa K (Journal of Institute of Medicine Nepal, 2021)
Introduction Chronic obstructive pulmonary disease (COPD) has great implications on global health accounting for significant morbidity and mortality. It is a state of chronic inflammation of airways. The aim of this study was to measure the plasma fibrinogen level in patient with COPD and find the relationship between plasma fibrinogen levels and severity of airflow obstruction. Methods This observational study was conducted from September 2017 to October 2018, where 80 eligible patients with the diagnosis of acute exacerbation of COPD (AECOPD) were included in the study and their plasma fibrinogen level was measured at the time of discharge. Clinical information was obtained and pulmonary function test (PFT) was done. Result A total of 80 patients were enrolled. The mean age of the patient was 67.87±11.60 years. Plasma fibrinogen level was 159±12.72 mg/dl in mild COPD, 273.52±62.34 mg/dl in moderate COPD, 312.30±103.67 mg/dl in severe COPD, and 487±102.76 mg/dl in very severe COPD. The comparison between groups showed significant difference in plasma fibrinogen level (p<0.001). There was significant negative correlation between plasma fibrinogen level and forced expiratory volume in one second (FEV1%) predicted (r=-0.71, p=0.01). Conclusion High plasma fibrinogen level on discharge was found in COPD patients with severe airflow obstruction, frequent exacerbations and severe level of dyspnoea during AECOPD.